AB0128 CXCL5 DAMPENS INFLAMMATION IN THE PRE-CLINICAL MODEL OF SYSTEMIC LUPUS ERYTHEMATOSUS VIA THE ORCHESTRAL EFFECT OF REGULATING NEUTROPHIL TRAFFICKING AND SUPPRESSING HELPER T CELL-MEDIATED IMMUNE RESPONSE. (2nd June 2020) - Fan, X.; Guo, D.; Ng, C. T.; Law, A.; Poon, Z. Y.; Cheung, A.; Lim, K. H.; Thumboo, J.; Hwang, W.; Low, A.
Abstract : Background: Patients with systemic lupus erythematosus (SLE) suffer from severe morbidity and mortality 1-4, either from the disease itself or from side effects of immunosuppression 5 . Discovery of novel effective therapies with less toxicity is an urgent need. Objectives: The aim of this study is to elucidate the therapeutic potential and working mechanism of cytokine CXCL5 in lupus mice. Methods: Treatment with CXCL5, bone marrow (BM)-MSCs, standard of care (SOC) with combination of methylprednisolone and cyclophosphamide was given to 16-week-old Fas lpr mice. Mice were monitored for 10 weeks. Splenic immune cell subsets were measured by flow cytometry. Circulating cytokine and immunoglobulin were detected by Luminex technology. Renal function was evaluated by urinary spot albumin creatinine ratio. In situ renal immune cell infiltration and complement 3 deposition were detected by Haematoxylin and Eosin (H&E) staining and immunohistochemistry. Results: CXCL5 demonstrated consistent and potent immunosuppressive capacity in suppressing SLE with reduced autoantibody secretion, lymphoproliferation and preserved kidney function. With further exploration, we proved that CXCL5 reduced the proliferation of helper T cells (TH 1 and TH 2) in the in vitro functional assay. When we administrated CXCL5 to lupus mice, it promoted the proliferation of regulatory T cells and reduced the proliferation of TH 17 cells, macrophages and neutrophils. Multiple proinflammatory cytokines including IL-2, IL-6, IL-12, IL-17A, KC/CXCL1, MIP-1β/CCL4 and TNF-α were also reduced. When combined with SOC, CXCL5 boosted its therapeutic effect and reduced the relevant indices of disease activity. When we correlated the effect of four different treatment groups (CXCL5, BM-MSCs, SOC, and CXCL5 plus SOC) on mice survival and target cell changes, we found that TH 17 cells were the key effector cells involved in the pathogenesis of SLE. Conclusion: These findings demonstrated that CXCL5 dampens inflammation in the pre-clinical model of systemic lupus erythematosus via the orchestral effect of regulating neutrophil trafficking and suppressing helper T cell-mediated immune response. Administrating exogenous CXCL5 might be an attractive option to treat patients with lupus. References: [1]Ji S, Guo Q, Han Y, Tan G, Luo Y, Zeng F. Mesenchymal stem cell transplantation inhibits abnormal activation of Akt/GSK3beta signaling pathway in T cells from systemic lupus erythematosus mice. Cell Physiol Biochem. 2012;29(5-6):705-712. [2]Peng SL. Altered T and B lymphocyte signaling pathways in lupus. Autoimmun Rev. 2009;8(3):179-183. [3]Ferucci ED, Johnston JM, Gaddy JR, et al. Prevalence and incidence of systemic lupus erythematosus in a population-based registry of American Indian and Alaska Native people, 2007-2009. Arthritis Rheumatol. 2014;66(9):2494-2502. [4]Jakes RW, Bae SC, Louthrenoo W, Mok CC, Navarra SV, Kwon N. Systematic review of the epidemiology of systemic lupus erythematosus in the Asia-Pacific region: prevalence, incidence, clinical features, and mortality. Arthritis Care Res (Hoboken). 2012;64(2):159-168. [5]Sattwika PD, Mustafa R, Paramaiswari A, Herningtyas EH. Stem cells for lupus nephritis: a concise review of current knowledge. Lupus. 2018;27(12):1881-1897. Acknowledgments: The work was supported by SMART II Centre Grant (NMRC/CG/M011/2017_SGH) and SingHealth Foundation (SHF/FG638P/2016). Disclosure of Interests: None declared